The internship dentists self confidence levels during root canal treatment procedures - Doumani, Mazen; Habib, Adnan; Alhababi, Abrar; Bashnakli, Ahmad; Shamsy, Enass; Nassani, Mohammad Zakaria (International Journal of Dental Research, 2017)
Self-confidence level assessment in newly graduated students is very important to evaluate the undergraduate endodontic courses. Objective: The aim of this study was to get information from internship dentists in Alfarabi dental college related to their confidence levels during root canal treatment procedures.Methods: Anonymous survey forms were sent to 150 internship dentists in Alfarbi dental college. They were asked to indicate their self-confidence level by Lickert’s scoring system ranging between 1 and 5.Results: Removal of broken instruments was determined as a procedure that was not experienced by 25.2% of the dentists. (44.6%) of dentists felt confident about taking radiographs during root canal treatment. 1.9 % of them reported as having very little confidence during retreatment. The irrigation was a procedure in which they felt very confident about (59.2%).Conclusion: The non-practiced endodontic procedure was clearly related to levels of self confidence among internship dentists; this means; a lot of studies in dental school should be performed to determine the weakness points or gaps in undergraduate endodontic courses.